"Times are changing" : the impact of HIV diagnosis on Sub-Saharan migrants' lives in France - (:unkn) unknown (My University, 2017)
Background Migrants account for 35% of HIV diagnoses in the European Union (ECDC/WHO 2014). Little is known about the impact of such a lifelong infection diagnosis on lives that are already disrupted by migration. In this paper, we assess the impact of HIV diagnosis on activity, union, well-being among African migrants living in France, the second group most affected by HIV after MSM. We compare it with the impact of the diagnosis of Hepatitis B, another lifelong infection affecting African migrants. Methods We use the ANRS PARCOURS survey, a retrospective life-event survey led in 2012-2013 in 74 health structures in Paris greater area which collected 926 life histories of Sub-Saharan migrants living with HIV and 779 with Hepatitis B. We modelled the probability year by year since 18 years of age until data collection to lose one's activity, to experience a conjugal break up and degradation of well-being and we estimated the impact of migration and of HIV and Hepatitis B diagnoses on these probabilities, after adjustment on other factors, thanks to discrete-time logistic regressions. Results Migration entailed loss of activity and conjugal break up, though HIV diagnosis after migration did not statistically impact on these outcomes. Yet HIV diagnosis had a massive negative impact on well-being (aOR = 11.31 [4.64-27.56] for men and 5.75 [2.79 -11.86] for women). This negative impact on well-being tended to diminish for persons diagnosed after 2004. The negative impact of HIV diagnosis on African migrants' well-being seems to be attenuated in the last decade, which hints at a normalization of the subjective experience of HIV diagnosis.
Keywords: African Research